MicroRNA-92b promotes cell proliferation and invasion in osteosarcoma by directly targeting Dickkopf-related protein 3 - Wu, Qing (Exp Ther Med, 2018)
Deregulation of microRNA-92b (miR-92b) has been implicated in osteosarcoma. However, the underlying regulatory mechanism of miR-92b in osteosarcoma growth and metastasis remains largely unclear. In the present study, reverse transcription-quantitative polymerase chain reaction and western blotting were used to measure mRNA and protein expression. MTT and Transwell assays were conducted to determine cell proliferation and invasion, and a luciferase reporter assay was performed to confirm the association between miR-92b and Dickkopf3-related protein (DKK3). The results demonstrated that miR-92b was significantly upregulated in osteosarcoma tissues compared with matched adjacent non-tumor tissues. Additionally, high miR-92b levels were significantly associated with lung metastasis and advanced tumor, node, metastasis stage (P<0.05) but not with age, sex, tumor size, location, serum lactate dehydrogenase or serum alkaline phosphatase. miR-92b expression was also significantly upregulated in osteosarcoma cell lines compared with normal osteoblast cells. Knockdown of miR-92b significantly inhibited the proliferation and invasion of osteosarcoma U2OS cells (P<0.01). By contrast, overexpression of miR-92b significantly increased U2OS cell proliferation and invasion (P<0.01). DKK3 was identified as a target gene of miR-92b and it was demonstrated that DKK3 expression was negatively regulated by miR-92b in U2OS cells. Restoration of DKK3 expression abrogated the increased proliferation and invasion of U2OS cells induced by miR-92b overexpression. Notably, DKK3 was significantly downregulated in osteosarcoma tissues compared with adjacent non-tumor tissues and its expression was inversely correlated to miR-92b levels in osteosarcoma tissues. Taken together, these data indicate that miR-92b promotes cell proliferation and invasion in osteosarcoma by targeting DKK3. Therefore, miR-92b may become a potential therapeutic target for osteosarcoma.